Mentoring Teachers for English Language Acquisition through LSRW Insights from Literature Review - Gurung, Pratima; Kaur, Tejinder; Kumar, Ravindra; Shrivastava, Chandan (JOURNAL OF INDIAN EDUCATION, 2023)
The English language enjoys the status of the Lingua Franca, the international language, the language of technology, which clearly indicates its importance in every sphere all over the world. As ‘LSRW’ skills, i.e., ‘Listening, Speaking, Reading and Writing’, are one of the basic skills for English language acquisition, it is essential for learners belonging to various disciplines to master them for achieving success in the 21st century. NEP 2020 emphasises the enhancement of soft skills of learners and communication is one of them, hence LSRW skills are important. Even in crises like the COVID-19 pandemic, the education system revived its status with the help of digital technologies, innovative pedagogical interventions, modern digital methods and approaches of teaching and learning LSRW skills worked for effective English Language acquisition. This paper recognises the role and importance of teacher quality to address the enhancement of LSRW skills.